(untitled) (Research, Society and Development, 2022)
Objective: To identify the impact of COVID-19 on the treatment of Myocardial Ischemia in global health systems during the pandemic. Method: Integrative review, carried out in the VHL, CINAHL, MEDLINE and SCOPUS databases, with articles published between November 2019 and April 2021. Results: The sample consisted of 12 original articles, from China, Japan, England, Turkey, Spain, Ireland, United States and France. The number of admissions for cardiovascular events, including ST-segment elevation Myocardial Infarction (STEMI), was reduced. In addition, there was an increase in the time to revascularization and a decrease in the performance of percutaneous coronary intervention (PCI). COVID-19 was associated with worse outcomes in patients with STEMI, such as longer hospital stays, longer intensive care unit stays, and higher mortality. Conclusion: The worldwide treatment of Myocardial Ischemia was affected by the COVID-19 pandemic, since there was a reduction in admissions for cardiovascular problems, increases in ischemia time, reduction of PCI and worse outcomes in patients with STEMI positive for COVID-19.